2009
DOI: 10.1177/0003065109337508
|View full text |Cite
|
Sign up to set email alerts
|

Dropout Rate of Training Cases: Who and When

Abstract: Training cases define clinical immersion for candidates and are essential to their education, progression, and graduation. While dropouts from treatment are expected, repeated dropouts can be detrimental to a candidate's education and progression. In a study of the rate and timing of dropout in 145 cases at the Columbia University Center for Psychoanalytic Training and Research, 40 percent of patients were found to have dropped out within the first twelve months of treatment, though converted cases were less l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Fluctuations in these measures in the analyst's notes could provide indicators of possible turning points in a treatment, including points of difficulty or opportunity that might usefully be addressed in supervision. A recent paper by Hamilton, Winiger, and Roose (2009) examined the problem of the high rate of dropout in training cases and addressed the need for supervision concerning the induction phase of psychoanalysis. High dropout rate is also recognized as a widespread problem in all forms of psychotherapy (Abbass, Hancock, Henderson, & Kisely, 2006;Lambert & Ogles, 2004;Schottenbauer, Glass, Arnkoff, Tendick, & Gray, 2008).…”
Section: Potential Clinical and Research Applicationsmentioning
confidence: 99%
“…Fluctuations in these measures in the analyst's notes could provide indicators of possible turning points in a treatment, including points of difficulty or opportunity that might usefully be addressed in supervision. A recent paper by Hamilton, Winiger, and Roose (2009) examined the problem of the high rate of dropout in training cases and addressed the need for supervision concerning the induction phase of psychoanalysis. High dropout rate is also recognized as a widespread problem in all forms of psychotherapy (Abbass, Hancock, Henderson, & Kisely, 2006;Lambert & Ogles, 2004;Schottenbauer, Glass, Arnkoff, Tendick, & Gray, 2008).…”
Section: Potential Clinical and Research Applicationsmentioning
confidence: 99%
“…Usually, therapist and patient have different perceptions of the nature of the patient's problems, the treatment, and the outcome, which may lead to that patient ending treatment more quickly than the therapist expects (Barrett et al, 2008;Hamilton, Wininger, & Roose, 2009;Mueller & Pekarik, 2000;Shamir, Szor, & Melamed, 2010). Many dropouts show improvements comparable to patients remaining in treatment and are contented with their contact or return within a year (Baekeland & Lundwall, 1975;Clarkin & Levy, 2004;Klein et al, 2003;Reis & Brown, 1999;Wierzbicki & Pekarik, 1993;Young et al, 2000).…”
mentioning
confidence: 99%
“…The intake procedures for patients have remained the same and are described in our earlier paper (Hamilton, Wininger, and Roose 2009). Patients in the current sample are all patients who were accepted for analytic treatment and either dropped out before twelve months or remained in treatment after twelve months (ongoing cases).…”
Section: Methodsmentioning
confidence: 99%
“…While dropouts from treatment are expected, repeated dropouts can be demoralizing and detrimental to a candidate's education and progression. Four years ago we published a paper reporting the dropout rate of training cases at the center who began treatment between September 2002 and July 2008 (Hamilton, Wininger, and Roose 2009). In that study of 141 cases we found that 40% of training cases drop out of treatment before the end of the first year of analysis; a striking fact was that half of these patients dropped out in the first month of treatment.…”
Section: Selected Posters From the 2013 Poster Session Of The Americamentioning
confidence: 99%